IMPLEMEMTASI STRATEGI PETA KONSEP UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPS KELAS IVC SD NEGERI 130 PEKANBARU - Olive, Irvingia Malayana Olive Malayana; Kurniaman, Otang Kurniaman Otang; ', Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was learning process in social studies at the classroom of fourth graderes (IVc) SD Negeri 130 Pekanbaru was conventional that’s cause student’s achievement still low with average value 62,07 (with KKM 70). The purpose of this research was to improve the learning process in social studies of fourth graderes (IVc) SD Negeri 130 Pekanbaru with the implementation strategy of Concept Mapping. This research was on classroom action research with two cycles in second semester 2014/2015. After implementation the strategy of Concept Mapping, student’s achievement average on test I was 70,62 that improved 13,77% from pre test. Student achievement average on test II was 75,12 that improved 21,02% from pre test. At first cycle, teacher’s activity with the implementation strategy of Concept Mapping on the first meeting was 80% (good category) and on the second meeting was 87,5 (good category). At second cycle, teacher activity on the first meeting was 90% (verygood category) and got 90% (verygood category) on the second meeting. Student’s activity in first meeting of first cycle was 62,5% (enough category) and got 70% (good category) on the second meeting. At second cycle, student’s activity in first meeting was 77,5% (good category) and got 85% (good category) on the second meeting. So, the implementation strategy of concept mapping can improved the learning process in social studies of fourth graderes (IVc) SD Negeri 130 Pekanbaru.Key Word : Strategy Of Concept Mapping, Social Studies Learning Processy.